2013
DOI: 10.1073/pnas.1222647110
|View full text |Cite
|
Sign up to set email alerts
|

Extensive diversity in circadian regulation of plasma lipids and evidence for different circadian metabolic phenotypes in humans

Abstract: The circadian system regulates daily rhythms in lipid metabolism and adipose tissue function. Although disruption of circadian clock function is associated with negative cardiometabolic end points, very little is known about interindividual variation in circadianregulated metabolic pathways. Here, we used targeted lipidomicsbased approaches to profile the time course of 263 lipids in blood plasma in 20 healthy individuals. Over a span of 28 h, blood was collected every 4 h and plasma lipids were analyzed by HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
183
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(215 citation statements)
references
References 38 publications
24
183
2
1
Order By: Relevance
“…4). This value is similar to a study in human plasma, which showed 17.8% of oscillating lipid metabolites when analyzed on an individual basis (19). To unravel whether these metabolite oscillations are solely driven by diurnal cycles of rest-activity and food intake, or are controlled in a cellautonomous manner, we conducted a similar temporal analysis in primary human skeletal myotubes synchronized in vitro.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…4). This value is similar to a study in human plasma, which showed 17.8% of oscillating lipid metabolites when analyzed on an individual basis (19). To unravel whether these metabolite oscillations are solely driven by diurnal cycles of rest-activity and food intake, or are controlled in a cellautonomous manner, we conducted a similar temporal analysis in primary human skeletal myotubes synchronized in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…In humans, diurnal variations in glucose tolerance have long been described (18), and rhythmic profiles of plasma glucose, insulin, and triglycerides have been detected (19,20). Furthermore, a lipidomic analysis of human plasma has shown that ∼18% of all lipid profiles oscillate in a circadian manner independent of sleep and food intake (19).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In another study, lipidomics analyses revealed that about 17 % of lipids showed circadian oscillations in wild-type mice and in Per1 −/− /Per2 −/− mice fed ad libitum. Consistent with studies in human subjects (108) , TAG species were especially rhythmic, but their peak accumulation was shifted in clock gene-deficient animals (112) . Exposure to a high-fat diet also has a profound influence on diurnal variation in the liver metabolome (82,113) .…”
Section: Using Lipidomics To Characterise Metabolic Pathwayssupporting
confidence: 84%
“…Therefore, future studies should examine the interaction of genetic and environmental factors on diurnal regulation of lipids and postprandial responses. If it were possible to identify prospectively individuals who are at increased risk of metabolic dysregulation caused by circadian misalignment and night eating, such information (108) .…”
Section: Limitations and Future Directionsmentioning
confidence: 99%